SENDING MONEY SYSTEM DESIGN INFORMATION ON BANK XYZ - Christian Denny Abadi; Irwan Bastian, Skom, MM (Jurnal Sistem Informasi, 1997)
Utilization of money remittance services on a very large bank applications, as well aswe can be spared from evil, we too can enjoy the results are quite satisfactory despitethe shipping cost a bit more expensive compared to banks other money transferservices. With today's technological advances, particularly the role of banks in themoney transfer has been increasingly developed and improved, has seen many majorbanks that use advances in technology (computers) in the process works.